An opportunity in difficulty: Japan–Korea–Taiwan expert Delphi consensus on surgical difficulty during laparoscopic cholecystectomy. (19th March 2017) - Iwashita, Yukio; Hibi, Taizo; Ohyama, Tetsuji; Honda, Goro; Yoshida, Masahiro; Miura, Fumihiko; Takada, Tadahiro; Han, Ho‐Seong; Hwang, Tsann‐Long; Shinya, Satoshi; Suzuki, Kenji; Umezawa, Akiko; et al.
Abstract: Background: We previously identified 25 intraoperative findings during laparoscopic cholecystectomy (LC) as potential indicators of surgical difficulty per nominal group technique. This study aimed to build a consensus among expert LC surgeons on the impact of each item on surgical difficulty. Methods: Surgeons from Japan, Korea, and Taiwan ( n = 554) participated in a Delphi process and graded the 25 items on a seven‐stage scale (range, 0–6). Consensus was defined as (1) the interquartile range (IQR) of overall responses ≤2 and (2) ≥66% of the responses concentrated within a median ± 1 after stratification by workplace and LC experience level. Results: Response rates for the first and the second‐round Delphi were 92.6% and 90.3%, respectively. Final consensus was reached for all the 25 items. 'Diffuse scarring in the Calot's triangle area' in the 'Factors related to inflammation of the gallbladder' category had the strongest impact on surgical difficulty (median, 5; IQR, 1). Surgeons agreed that the surgical difficulty increases as more fibrotic change and scarring develop. The median point for each item was set as the difficulty score. Conclusions: A Delphi consensus was reached among expert LC surgeons on the impact of intraoperative findings on surgical difficulty. Abstract : Highlight Iwashita and colleagues achieved Delphi consensus among expert surgeons from Japan, Korea and Taiwan on 25 intraoperative findings contributing to surgical difficulty during laparoscopic cholecystectomy. This consensus should form the basis of a novel and universal grading system of surgical difficulty and serve as the gold standard for future multicenter trials.